A comprehensive strategy for the development of a multi-epitope vaccine targeting Treponema pallidum, utilizing heat shock proteins, encompassing the entire process from vaccine design to in vitro evaluation of immunogenicity - Jiang, Jing; Xu, Linglan; Wang, Xuefeng; Wang, Ming; Cao, Youde; Li, Ranhui; Zheng, Kang; Wu, Xian (Frontiers in Microbiology, 2025)
BackgroundTreponema pallidum, the causative spirochete of syphilis, is primarily transmitted through sexual contact and has emerged as a significant global health concern. To address this issue, enhancing diagnostic capabilities, strengthening public health interventions, and developing a safe and effective vaccine are critical strategies.ObjectiveThis study employed an immunoinformatics approach to design a vaccine with high immunogenic potential, targeting the heat shock proteins of T. pallidum.MethodsBased on heat shock proteins of T. pallidum, we predicted B-cell, CTL, and HTL epitopes and all the selected epitopes were linked to construct a multi-epitope vaccine. Antigenicity, toxicity, and allergenicity of epitopes were checked by VaxiJen 2.0, AllerTOP v2.0, and ToxinPred servers. After constructing the multi-epitope vaccine, we subsequently predicted its secondary and tertiary protein structures. After refining and validating the modeled structure, we utilized advanced computational approaches, including molecular docking and dynamic simulations, to evaluate the binding affinity, compatibility, and stability of the vaccine-adjuvant complexes. Eventually, in silico cloning was conducted to optimize protein expression and production.ResultsThe multi-epitope subunit vaccine we developed was constructed by seven cytotoxic T lymphocyte epitopes, five helper T lymphocyte epitopes, four B cell epitopes, and adjuvant β-defensin. An adjuvant was used to enhance immune responses, all of which were linked to one another using GPGPG, AAY, and KK linkers, respectively. The population coverage of the designed vaccine was 94.41% worldwide. Molecular docking and MD simulations indicated strong binding interactions with TLR1/2, TLR-2 and TLR-4 in a stable vaccine-receptor complex. The final designed vaccine, composed of 502 amino acids, theoretically exhibits high antigenicity and immunity, capable of inducing both humoral and cellular immune responses.ConclusionThe vaccine developed in this study theoretically represents a safe and potent multi-epitope prophylactic strategy against T. pallidum, subject to further experimental validation to ascertain its actual protective efficacy.